Inspiratory effort impacts the accuracy of pulse pressure variations for fluid responsiveness prediction in mechanically ventilated patients with spontaneous breathing activity: a prospective cohort study - Hui Chen; Meihao Liang; Yuanchao He; Jean-Louis Teboul; Qin Sun; Jianfen Xie; Yi Yang; Haibo Qiu; Ling Liu (Annals of Intensive Care, 2023)
Abstract Background Pulse pressure variation (PPV) is unreliable in predicting fluid responsiveness (FR) in patients receiving mechanical ventilation with spontaneous breathing activity. Whether PPV can be valuable for predicting FR in patients with low inspiratory effort is unknown. We aimed to investigate whether PPV can be valuable in patients with low inspiratory effort. Methods This prospective study was conducted in an intensive care unit at a university hospital and included acute circulatory failure patients receiving volume-controlled ventilation with spontaneous breathing activity. Hemodynamic measurements were collected before and after a fluid challenge. The degree of inspiratory effort was assessed using airway occlusion pressure (P0.1) and airway pressure swing during a whole breath occlusion (ΔPocc) before fluid challenge. Patients were classified as fluid responders if their cardiac output increased by ≥ 10%. Areas under receiver operating characteristic (AUROC) curves and gray zone approach were used to assess the predictive performance of PPV. Results Among the 189 included patients, 53 (28.0%) were defined as responders. A PPV > 9.5% enabled to predict FR with an AUROC of 0.79 (0.67–0.83) in the whole population. The predictive performance of PPV differed significantly in groups stratified by the median value of P0.1 (P0.1 < 1.5 cmH2O and P0.1 ≥ 1.5 cmH2O), but not in groups stratified by the median value of ΔPocc (ΔPocc < − 9.8 cmH2O and ΔPocc ≥ − 9.8 cmH2O). Specifically, in patients with P0.1 < 1.5 cmH2O, PPV was associated with an AUROC of 0.90 (0.82–0.99) compared with 0.68 (0.57–0.79) otherwise (p = 0.0016). The cut-off values of PPV were 10.5% and 9.5%, respectively. Besides, patients with P0.1 < 1.5 cmH2O had a narrow gray zone (10.5–11.5%) compared to patients with P0.1 ≥ 1.5 cmH2O (8.5–16.5%). Conclusions PPV is reliable in predicting FR in patients who received controlled ventilation with low spontaneous effort, defined as P0.1 < 1.5 cmH2O. Trial registration NCT04802668. Registered 6 February 2021, https://clinicaltrials.gov/ct2/show/record/NCT04802668